Evaluation of skidding performance of asphalt surface using Griptester and British skid Pendulum device - Md. Zaid, Nur-ul Balqes (2013)
Good road means comfort for road users. The texture of road surface is very important for road users, to prevent road accidents from happening. If seen in highways, many tools are used to measure the slip road surface. Tools such as the British Pendulum and Grip tester are often used to test the slip road surface. These tools are the traditional tools and modern equipment, where by different way application, but with a purpose of which is to measure the slip road surface. The main objective of this study is to find relationship between British Pendulum and Griptester, and to develop evaluation model to predict the grip number using British Pendulum value. However, tests conducted by these two tools are only done on one type of surface material composed of ACW 20. This test was done at locations of the Expressway in Selangor and State Road in Melaka. Both of these tools are used for each location, after the data obtained from these tests are plotted to see the difference or relationship between these two devices. The analysis from this study indicates a very weak correlation. r2 value plotted form these two sites are below 0.19. The study recommends further investigation on more testing on different types of surfaces to improve the understanding on the correlation between the British Pendulum Value and Grip Number.